Systematic review of outcomes following observational and operative endoscopic middle ear surgery. (24th November 2014) - Kozin, Elliott D.; Gulati, Shawn; Kaplan, Alyson B.; Lehmann, Ashton E.; Remenschneider, Aaron K.; Landegger, Lukas D.; Cohen, Michael S.; Lee, Daniel J.
<x xml:space="preserve">Abstract</x> Objectives Middle ear surgery increasingly employs endoscopes as an adjunct to or replacement for the operative microscope. We provide a systematic review of endoscope applications in middle ear surgery with an emphasis on outcomes, including the need for conversion to microscope, audiometric findings, length of follow‐up, as well as disease‐specific outcomes. Data Sources PubMed, Embase, and Cochrane CENTRAL database. Methods A literature review was performed using the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis recommendations. Articles were categorized based on study design, indication, and use of an endoscope either as an adjunct to or as a replacement for a microscope. Qualitative and descriptive analyses of studies and outcomes data were performed. Results One‐hundred three articles met inclusion and exclusion criteria. Of the identified articles, 38 provided outcomes data. The majority of these studies were moderate quality, retrospective, case‐series reports. The indications for use of the endoscope were broad, with the most common being resection of cholesteatoma. In cholesteatoma surgery, endoscope approaches routinely identified residual cholesteatoma in primary and second‐look cases. Other outcomes, including robust audiometric data, operating room times, wound healing, and quality of life surveys were not well described. Conclusions Endoscopes have consistently been used as an adjunct to the microscope to improve visualization of the tympanic cavity. Recent reports utilize the endoscope exclusively during surgical dissection; however, data comparing patient outcomes following the use of an endoscope to a microscope are lacking. Areas in need of additional research are highlighted. Level of Evidence NA Laryngoscope, 125:1205–1214, 2015